Measuring Self-Serving Cognitive Distortions with Special Reference to Juvenile Delinquency: A Validation of the “How I Think” Questionnaire in a Sample of Portuguese Adolescents - Gomes, Hugo S. (International journal of offender therapy and comparative criminology, 2022)
The present study aims to test the psychometric properties of the Portuguese version of the “How I Think” (HIT) questionnaire. The HIT questionnaire is a self-report measure of self-serving cognitive distortions. Our sample was comprised of 442 Portuguese-speaking adolescents and young adults (254 males and 188 females), aged between 12 and 20 years. Of the total 442 participants, 351 were recruited from a Portuguese school and 91 from four Portuguese detention centers for juvenile delinquents. Data analysis provided evidence supporting the original six-factor model solution, composed of a four-category typology of self-serving cognitive distortions (i.e., Selfcentered, Blaming Others, Minimizing/Mislabeling, and Assuming the Worst), an Anomalous responding, and one Positive filler factor. Further, results showed satisfactory internal consistency, convergent validity, and discriminant validity. In conclusion, this article provides Portuguese researchers and practitioners with a valid measure of self-serving cognitive distortions.